Implementasi Meningkatkan Sumber Daya Manusia Melalui Program Mengembangkan Kecerdasan Logika Metematika Anak Usia Dini Menggunakan Media Kartu Angka - Mina Laili, Mahsiani; Magdalena, Marini; Kholifah, Siti (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Mathematical logic intelligence is one of the intelligences that every human resource must have which should be prepared from an early age so that children are trained from an early age to be able to think critically using their logic. This research analyzes the mathematical logic abilities of early childhood using a combination of qualitative and quantitative. The methods used in this research are surveys and case studies, as well as questionnaires and observation measuring tools as techniques for collecting data. This research involved 10 children consisting of 5 girls and 5 boys and then a pre-test was carried out using the Gardner H (1993) mathematical logic intelligence instrument without number cards. Next, the 10 children were given game stimulation using number cards for 15 days and a post-test was carried out again. The results of the research showed that the mathematical logic intelligence of the ten children who had been stimulated using number cards increased very well. This can be seen from the ability to count, read numbers and solve problems logically which has a very good increase in score after being stimulated using number cards